2007
DOI: 10.1111/j.1532-5415.2007.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke‐Independent Association Between Metabolic Syndrome and Functional Dependence, Depression, and Low Quality of Life in Elderly Community‐Dwelling Brazilian People

Abstract: Met.S was significantly associated with functional dependence, depression, cognitive impairment, and low HRQoL, and its effects were independent of clinical stroke, IHD, and its own individual components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
64
3
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 46 publications
10
64
3
10
Order By: Relevance
“…In some studies, no association was found between any individual component and depression. 5,11 Yet other studies showed that low HDL, high blood pressure, high fasting glucose level, increased waist circumference, and obesity were associated with depressive symptoms. [7][8][9][10] Differences in sampling, region of residence, and variations in lifestyle can explain these inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In some studies, no association was found between any individual component and depression. 5,11 Yet other studies showed that low HDL, high blood pressure, high fasting glucose level, increased waist circumference, and obesity were associated with depressive symptoms. [7][8][9][10] Differences in sampling, region of residence, and variations in lifestyle can explain these inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,9,10 Roriz-Cruz et al 5 investigated the association between MetS and depression in a sample of 420 individuals aged 60 years or above from two communities in southern Brazil. They found significantly worse scores for GDS as the number of clustered MetS components increased in the stroke-free population using an ANOVA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations